Milliwatt and nanosecond all-optical switching in a double-coupler ring resonator containing an EDFA - Li, Chunfei; Dou, Na; Yupapin, P. P. (My University, 2006)
We proposed an active double-coupler ring resonator all-optical switch, in which half of the fibre ring is made by a 980nm laser-pumped erbium-doped fibre to form an erbium-doped fibre amplifier (EDFA). The switching is based on self-modulation by the signal light at 1.55νm and has milliwatt switching power and nanosecond switching time for a 0.2m ring length. Because the gain of the EDFA compensates the losses in the ring and the EDF has high nonlinearity, the switching power can be reduced dramatically. Both switching time and switching power of such a switch can be controlled by adjusting the 980nm pumping power to make a trade-off between both parameters. © IOP Publishing Ltd.
Keywords: Double-coupler ring resonator; Erbium-doped fibre amplifier; Low-power all-optical switches; Switching power; Switching time